Along-Path Evolution of Biogeochemical and Carbonate System Properties in the Intermediate Water of the Western Mediterranean - Schroeder, Katrin; Cozzi, Stefano; Belgacem, Malek; Borghini, Mireno; Cantoni, Carolina; Durante, Sara; Petrizzo, Antonio; Poiana, Annalisa; Chiggiato, Jacopo (Frontiers in Marine Science, 2020)
A basin-scale oceanographic cruise (OCEANCERTAIN2015) was carried out in the Western Mediterranean (WMED) in summer 2015 to study the evolution of hydrological and biogeochemical properties of the most ubiquitous water mass of the Mediterranean Sea, the Intermediate Water (IW). IW is a relatively warm water mass, formed in the Eastern Mediterranean (EMED) and identified by a salinity maximum all over the basin. While it flows westward, towards and across the WMED, it gradually loses its characteristics. This study describes the along-path changes of thermohaline and biogeochemical properties of the IW in the WMED, trying to discriminate changes induced by mixing and changes induced by interior biogeochemical processes. In the first part of the path (from the Sicily Channel to the Tyrrhenian Sea), respiration in the IW interior was found to have a dominant role in determining its biogeochemical evolution. Afterwards, when IW crosses regions of enhanced vertical dynamics (Ligurian Sea, Gulf of Lion and Catalan Sea), mixing with surrounding water masses becomes the primary process. In the final part of the investigated IW path (the Menorca-Mallorca region), the role of respiration is further masked by the effects of a complex circulation of IW, indicating that short-term sub-regional hydrological processes are important to define IW characteristics in the westernmost part of the investigated area. A pronounced along-path acidification was detected in IW, mainly due to remineralization of organic matter. This induced a shift of the carbonate equilibrium towards more acidic species and makes this water mass increasingly less adequate for an optimal growth of calcifying organisms. The carbonate buffering capacity also decreases as IW flows through the WMED, making it more exposed to the adverse effects of a decreasing pH. The present analysis indicates that IW evolution in the sub-basins of the WMED is currently driven by complex hydrological and biogeochemical processes, which could be differently impacted by coming climate changes, in particular considering expected increases of extreme meteorological events, mainly due to the warming of the Mediterranean basin.